2007
DOI: 10.1007/s10592-006-9265-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for the persistence of the critically endangered Sierra Nevada red fox in California

Abstract: California is home to both the native statethreatened Sierra Nevada red fox (Vulpes vulpes necator), which historically inhabited high elevations of the Sierra Nevada and Cascade mountains, and to multiple low-elevation red fox populations thought to be of exotic origin. During the past few decades the lowland populations have dramatically expanded their distribution, and possibly moved into the historic range of the native high-elevation fox. To determine whether the native red fox persists in its historic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 53 publications
1
102
2
Order By: Relevance
“…This belief later appeared to be supported by a morphometric study, which demonstrated that Sacramento Valley foxes were significantly larger than montane foxes but similar in size to Midwestern foxes (Roest 1977), suggesting that exotic red foxes could have been transported to the Valley via transcontinental railway, after it reached the city of Sacramento in 1869 (Roest 1977;Lewis et al 1999;Kamler and Ballard 2002). However, recent mitochondrial analyses of historical and modern specimens from the Sacramento Valley indicated this population was distinct from other nonnative populations in California, which were clearly of Eastern and Northern origins (Perrine et al 2007;Aubry et al 2009). Moreover, the most common haplotype (D) in the Sacramento Valley differed by a single substitution from the dominant haplotype (A) of the Western mountains.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This belief later appeared to be supported by a morphometric study, which demonstrated that Sacramento Valley foxes were significantly larger than montane foxes but similar in size to Midwestern foxes (Roest 1977), suggesting that exotic red foxes could have been transported to the Valley via transcontinental railway, after it reached the city of Sacramento in 1869 (Roest 1977;Lewis et al 1999;Kamler and Ballard 2002). However, recent mitochondrial analyses of historical and modern specimens from the Sacramento Valley indicated this population was distinct from other nonnative populations in California, which were clearly of Eastern and Northern origins (Perrine et al 2007;Aubry et al 2009). Moreover, the most common haplotype (D) in the Sacramento Valley differed by a single substitution from the dominant haplotype (A) of the Western mountains.…”
Section: Introductionmentioning
confidence: 83%
“…These montane foxes are phylogenetically, morphologically, and ecologically distinct from red foxes native to eastern and northern North America (Roest 1977;Swanson et al 2005;Perrine et al 2007;Aubry et al 2009). In the 1900s, North American red foxes of Eastern and Northern ancestry were introduced to and have thrived in several warm, lowland regions of Washington, Oregon, and California (Aubry 1984;Lewis et al 1999;Kamler and Ballard 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For mitochondrial analysis, we amplified a cytochromeb (354 bp) fragment in the mitochondria in 102 individuals sampled throughout Sweden using primers RF14724 (5 0 -CAACTATAAGAACATTAATGACC-3 0 ) and RF15149 (5 0 -CTCAGAATGATATTTGTCCTC-3 0 ) (Perrine et al 2007;Aubry et al 2009) on a PTC100 Programmable Thermal Controller (MJ Research Inc.). Each PCR setup was accompanied by negative controls from the extraction as well as PCR blanks.…”
Section: Sampling and Genetic Analysesmentioning
confidence: 99%
“…The Sacramento Valley red fox Vulpes vulpes patwin is an ecologically distinct subspecies endemic to California (Figure 1; Perrine et al 2007;Sacks et al 2010a). This fox is one of four subspecies in a phylogenetically divergent lineage native to the western United States.…”
Section: Introductionmentioning
confidence: 99%